2017
DOI: 10.1002/2016ja023329
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic fluid modeling of ionospheric upflow: Effects of low‐altitude anisotropy and thermospheric winds

Abstract: A new anisotropic fluid model is developed to describe ionospheric upflow responses to magnetospheric forcing by electric fields and broadband ELF waves at altitudes of 90–2500 km. This model is based on a bi‐Maxwellian ion distribution and solves time‐dependent, nonlinear equations of conservation of mass, momentum, parallel energy, and perpendicular energy for six ion species important to E, F, and topside ionospheric regions. It includes chemical and collisional interactions with the neutral atmosphere, pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 65 publications
(126 reference statements)
0
18
0
Order By: Relevance
“…The ionospheric model used in this study and described in detail in Burleigh and Zettergren () (GEMINI‐TIA) is an anisotropic extension of the model originally developed in Zettergren and Semeter () and expanded in Zettergren and Snively (), Zettergren et al (), and Zettergren and Snively (). This fluid model solves the 2‐D nonlinear equations for the conservation of mass, momentum, parallel energy, and perpendicular energy for each species s relevant to the E and F regions and topside ionosphere ( s = O + , NO + , N 2+ O 2+, N + , and H + ) and is coupled to a quasi‐static treatment of auroral and neutral dynamo electric currents.…”
Section: Modeling Approachmentioning
confidence: 99%
See 3 more Smart Citations
“…The ionospheric model used in this study and described in detail in Burleigh and Zettergren () (GEMINI‐TIA) is an anisotropic extension of the model originally developed in Zettergren and Semeter () and expanded in Zettergren and Snively (), Zettergren et al (), and Zettergren and Snively (). This fluid model solves the 2‐D nonlinear equations for the conservation of mass, momentum, parallel energy, and perpendicular energy for each species s relevant to the E and F regions and topside ionosphere ( s = O + , NO + , N 2+ O 2+, N + , and H + ) and is coupled to a quasi‐static treatment of auroral and neutral dynamo electric currents.…”
Section: Modeling Approachmentioning
confidence: 99%
“…In a third new simulation, denoted by SS W , the control simulation also has wave heating applied at the same UT for additional comparison. The wave heating is accomplished through the use of the resonant heating term, trueẆs,, included in the perpendicular energy equation within the model that encompasses the acceleration of ions by transverse plasma waves (Burleigh & Zettergren, ). This gyroresonant (cyclotron) energy transfer is the most efficient in regions of low ion‐neutral collision rates and is therefore not very effective below 500 km except in extreme cases (e.g., Whalen et al, ).…”
Section: Ionospheric Response To Gw Forcingmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous ionospheric modeling studies (e.g., Burleigh & Zettergren, ; Wu et al, ) and comparisons against observations (e.g., Sanchez & Strømme, ) have demonstrated that ionospheric sources of plasma to the topside (controlled by low‐altitude heating and dynamics) can regulate outward ion fluxes. Most upflow studies examine the “step response” of the ionosphere, by using a fixed precipitation input having some “ramp‐up“ time scale or “on‐off” paradigm (e.g., Caton et al, ; Sadler et al, ) — a sensible approach but one that cannot account for situations with complicated time‐variable forcing.…”
Section: Introductionmentioning
confidence: 99%